2019
DOI: 10.1016/j.celrep.2018.12.059
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt-Driven Mll1 Epigenome Regulates Salivary Gland and Head and Neck Cancer

Abstract: Highlights d High Wnt/b-catenin and Mll1 are linked to high H3K4me3 at promoters in mouse tumors d Mll1 is required for the initiation and maintenance of salivary gland tumors d SET domain mutations of Mll1 reduce the self-renewal of tumor-propagating cells d Genetic Mll1 ablation reduces tumor initiation of human head and neck cancer cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 78 publications
2
19
0
Order By: Relevance
“…5a, Supplementary Fig 11a). In agreement with our model, in which tumors are induced by activation of β-catenin and Bmpr1a mutations via the basalspecific K14-cre promoter 16,17 , we find that this trajectory initiates in basal tumor cells, further proceeds through the two CSClike subpopulations, and ends in the luminal Clu+ cell cluster with continuous transitions in between (Fig. 5a, b).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…5a, Supplementary Fig 11a). In agreement with our model, in which tumors are induced by activation of β-catenin and Bmpr1a mutations via the basalspecific K14-cre promoter 16,17 , we find that this trajectory initiates in basal tumor cells, further proceeds through the two CSClike subpopulations, and ends in the luminal Clu+ cell cluster with continuous transitions in between (Fig. 5a, b).…”
Section: Resultssupporting
confidence: 91%
“…In line with our transcriptome data, Clu and Wfdc18 distinctively stained K8positive luminal-like cells within the tumor region. Nuclear βcatenin is considered to be the hallmark of active Wnt signaling which ultimately drives the expression of its target genes 35,36 and was previously described to be a key feature of CSCs in several cancers including our model 16,17,37 . We, therefore, used this as an additional marker, and found that nuclear β-catenin-positive cells were generally K8 negative and greatly overlapped with high Axin2, but only partially with Ptn and Wif1 stainings.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Together, these proteins were shown to interact in promoting self-renewal in HNSCC tumor propagating cells, which were highly proliferative and highly tumorigenic. The formation of this complex could be blocked by ICG-001 [130] or LF3, an inhibitor of interaction between β-catenin and TCF4 [132], which resulted in the loss of the capacity of tumor propagating cells for self-renewal and reduced tumor formation in vivo.…”
Section: Functional Significance Of Wnt/β-catenin Pathway Dysregulationmentioning
confidence: 99%